2020
DOI: 10.4102/sajbm.v51i1.1943
|View full text |Cite
|
Sign up to set email alerts
|

Coaching for development of leaders’ awareness of integrity: An evidence-based approach

Abstract: Purpose: There is a need for leading with integrity to contribute to sustainable effectiveness and performance in the organisational context. The purpose of this research was to provide insight into the elements that could facilitate the development of leaders’ awareness of integrity to support positive leader outcomes.Design/methodology/approach: Interpretative phenomenological analysis (IPA) was the research design, and purposive, convenience sampling was utilised to select six leaders. Data were collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…As shown in Figure 1, 15 studies met the inclusion criteria and were reviewed for this article. Predominantly, the investigations were peer-reviewed journal articles (Corbu et al, 2021;Elston & Boniwell, 2011;Fontes & Dello Russo, 2021;Guzmán et al, 2017;Kakarala et al, 2018;Palamara et al, 2015;Peláez Zuberbühler et al, 2020;Sparrow, 2007;Toogood, 2012;van der Walt & van Coller-Peter, 2020;van Nieuwerburgh et al, 2021;Yu et al, 2008), and one doctoral dissertation (Parsons, 2016) study. Following a thorough assessment of the papers, the results are presented in accordance with the following four key themes: 1) study characteristics; 2) PPC antecedents; 3) underlying mechanisms; and 4) PPC outcomes research.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 1, 15 studies met the inclusion criteria and were reviewed for this article. Predominantly, the investigations were peer-reviewed journal articles (Corbu et al, 2021;Elston & Boniwell, 2011;Fontes & Dello Russo, 2021;Guzmán et al, 2017;Kakarala et al, 2018;Palamara et al, 2015;Peláez Zuberbühler et al, 2020;Sparrow, 2007;Toogood, 2012;van der Walt & van Coller-Peter, 2020;van Nieuwerburgh et al, 2021;Yu et al, 2008), and one doctoral dissertation (Parsons, 2016) study. Following a thorough assessment of the papers, the results are presented in accordance with the following four key themes: 1) study characteristics; 2) PPC antecedents; 3) underlying mechanisms; and 4) PPC outcomes research.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies identified the antecedents of coaching results as being a significant aspect of the process (Corbu et al, 2020;Elston & Boniwell, 2011;Fontes & Dello Russo, 2021;Toogood, 2012;van der Walt & van Coller-Peter, 2020). The majority of the studies (N = 4) were qualitative and employed semi-structured interviews to conduct an interpretive phenomenological analysis (IPA) of the elements that contribute to the effectiveness of the coaching process.…”
Section: Antecedentsmentioning
confidence: 99%
See 3 more Smart Citations